School Administration in the Implementation of the Bilingual Colombia Program in Private Educational Institutions in Cali (Colombia) - Miranda, Norbella; Echeverry, Ángela (Íkala, Revista de Lenguaje y Cultura, 2011)
This text aims to describe and analyze the management performed by school administrators for the implementation of the Bilingual Colombia Program (BCP) in private educational institutions of monolingual tradition located in strata 1 to 4 in Cali (Colombia). For this, we carried out a descriptive research which, through statistics and correlation, incorporated quantitative and qualitative interpretation of the information contained in surveys, the institutional educational projects and what the language education policy dictates. The research results showed advances in the implementation of the policy in some schools that have restructured their school dynamics and curriculum towards the attainment of better levels of language competence of their students; however, in most schools unawareness of key issues of school management to develop better language learning processes prevails. It can be concluded that there is a need to lead actions in the school community that acknowledge the new role of foreign language in education and to manage learning opportunities so that students can achieve the expected levels of language competence. Besides, stronger support from government agencies to this sector is needed.